Kendala Kepesertaan Program Jaminan Sosial Terhadap Pekerja di Sektor Informal: Studi Kasus di Kota Surabaya - Triyono -; Soewartoyo - (Faculty of Law, Trisakti University, 2013)
The social security is a national citizen’s right, include to the workers. However, in the reality is not all workers have been touched in the social security Indonesian programs. This paper will descript why the social security programs is not yet succeed for participation workers in Indonesia. This study is part of the results of research conducted by LIPI Population Research Center. This study approach used a desk literature review and the survey approach which be located at informal sector workers settlement in Surabaya. The analysis uses descriptive method that to discuss how the implementation of the social security programs were done by the government policies. This study found that the implementation of the social security not yet was followed by the majority of the informal sector workers. This is because due to the several constraints, such as, the workers are still not understand about of the National Social Security program; they have not get access to this program. Another factor is the education level of workers is low, its doe to their knowledge is lower. Therefore the situation brought the less access to information for the programs by the informal workers.Keywords : the social security program, the informal sector workers, information